Analisis Pembuktian Pidana Asal dalam Kasus Tindak Pidana Pencucian Uang yang Diatur dalam Undang-Undang: Tinjauan Terhadap Prinsip Hukum dan Implementasi dalam Praktik Hukum di Indonesia - Firman Anugerah; Dominikus Rato; Fendi Setyawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Money laundering is a serious threat to the financial stability and integrity of financial institutions in Indonesia. Proving the origin of criminal proceeds in money laundering cases is a primary focus in law enforcement efforts to combat this illegal activity. This paper provides a review of the legal principles underlying the proof of criminal origin in money laundering cases and discusses their implementation in legal practice in Indonesia.Through literature analysis and case studies, the author highlights the complexity of proving criminal origin in the context of money laundering cases. Challenges include difficulty in tracing complex financial transactions, limitations in adequate legal regulations, and the need for international cooperation for effective exchange of information and evidence. Additionally, the paper emphasizes the importance of meticulous financial analysis as a key instrument in proving the origin of laundered funds. In the context of legal practice implementation in Indonesia, this paper examines the efforts of the government and law enforcement agencies in handling money laundering cases. Despite steps taken to enhance law enforcement effectiveness, there are still challenges to be addressed, such as lack of coordination between agencies, protection of witnesses and informants, and the expertise required for complex financial analysis. Considering the relevant legal principles and challenges faced in legal practice in Indonesia, this paper concludes the need for greater efforts to enhance the capacity of law enforcement agencies, improve international cooperation, and strengthen regulatory frameworks to ensure the effectiveness of proving the criminal origin in money laundering cases in Indonesia.